Prenatal diagnose of a fetus with Harlequin ichthyosis in a Chinese family - Wei Jian; Qi-Ting Du; Zhen-Fei Lai; Yu-Fan Li; Shi-Quan Li; Zhong-Tang Xiong; Dun-Jin Chen; Min Chen; Jing-Si Chen (Elsevier, 2018)
Objective: Harlequin ichthyosis (HI) was the most severe form of ichthyoses, which leaded to neonatal death in 50% of cases. It was the result of mutations in ABCA12 gene. With the development of ultrasound skills and genetic analysis, HI could be prenatal diagnosed. Case report: Here, we reported a case of HI, which was prenatal diagnosed by ultrasound examination and genetic analysis. The fetus was found that severe ectropion, eclabium, flattened nose, and rudimentary ears by ultrasound at 20 weeks gestation. A molecular genetic analysis was performed and revealed two mutations in the ABCA12 gene. One of two mutations were not reported in the past. The fetus was terminated. Conclusion: HI was associated with the poor prognosis of HI neonates. Prenatal ultrasound and genetic analysis were important for prenatal diagnosis of HI and were helpful to give sufficient prenatal counsels for the family with HI baby.